A conversation: english in everyday life Book 2 - Carver, Tina Kasloff; Fotinos, Sandra Douglas (White Plains Pearson Education ESL, 1997)
Presents an inviting approach to developing conversation fluency. This book presents picture dictionary-type pages, along with conversation and grammar practice, that provide students with the vocabulary and speaking skills they need for everyday life. For intermediate ESL learners.